Narrative mechanisms in praise of the pure family according to Ali Al-Haidari - Hussein, إيمان محمد (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The poet Ali Abdul Amir Al-Haidari is considered one of the prominent figures of Iraq, an encyclopedia of importance in the contemporary cultural structure, in addition to his abundant poetry, which is characterized by a narrative and descriptive nature. Therefore, this study is dedicated to find out the narrative mechanisms in his poetry. The poetic collection “The Abundant Seas in Praise of the Pure Family” is the field for this research in these mechanisms present in description and dialogue, as the poet employs these two narrative mechanisms to serve his thoughts, beliefs, and inner beings, so he is creative in describing and dialogue with the Messenger (PBUH) and his pure family, drew clear pictures of these great historical figures, and succeeds in raising several issues that contributed to directing the recipient towards multiple messages of religious importance. The importance of description and dialogue lies in the functions performed by each of them.